2019
DOI: 10.1101/521609
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mesenchymal stem cells (MSCs) offer a drug tolerant and immune- privileged niche to Mycobacterium tuberculosis

Abstract: presence of MSCs co-inhabiting with Mtb. Together the results show targeting the 42"immune-privileged niche, provided by MSCs to Mtb, can revolutionize tuberculosis 43" prevention and cure. 44"and * at P<0.05. 645"

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 83 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…Unlike macrophages, mesenchymal stem cells (MSCs) provide cytosol as the niche for bacterial replication and rapid lipid synthesis for maintaining dormancy (Fatima et al, 2020). Bacteria live longer in MSCs in a dormant state by hiding themselves in lipid droplets and rendering themselves resistant to combination antibiotics therapy (Fatima et al, 2020) (Jain et al, 2020). It has also been suggested that MSCs are less tolerant to bacterial replication, unlike macrophages, but rather promote dormancy.…”
Section: Host-pathogen Interactions During Dormancymentioning
confidence: 99%
“…Unlike macrophages, mesenchymal stem cells (MSCs) provide cytosol as the niche for bacterial replication and rapid lipid synthesis for maintaining dormancy (Fatima et al, 2020). Bacteria live longer in MSCs in a dormant state by hiding themselves in lipid droplets and rendering themselves resistant to combination antibiotics therapy (Fatima et al, 2020) (Jain et al, 2020). It has also been suggested that MSCs are less tolerant to bacterial replication, unlike macrophages, but rather promote dormancy.…”
Section: Host-pathogen Interactions During Dormancymentioning
confidence: 99%
“…Since the median percentage of persisters were significantly different between CytD-and BafA1-treated groups, highlights mechanisms whereby M. tuberculosis may differentially modulate macrophage metabolic processes and antimicrobial functions (or vice versa), thus affecting the capacity of the host to resolve infection (Gleeson et al, 2016;Martin et al, 2017). The pharmacokinetics of anti-M. tuberculosis drugs may furthermore be influenced following BafA1 treatment, as drugs that accumulate in acidic vacuoles possessed a reduced killing capacity (Schump et al, 2017), whilst treatment with isoniazid or rifampicin led to a rapid decrease in drug tolerant M. tuberculosis (Mishra et al, 2019;Jain et al, 2020). It would thus be intriguing to determine the influence of these host processes on M. tuberculosis gene regulation to provide insight into how M. tuberculosis manipulates host immune signals and cytokines to evade immune detection and clearance.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many researchers have suggested that this change significantly reduces the virulence factors mannose-capped lipoarabinomannan (Man-LAM) and trehalose-6,6'-dimycolate (TDM) on the surface of MTB (Tuladhar and Kanneganti, 2020). For example, MTBsecreted ESAT-6 protein can improve the permeability of phagosomes in host phagocytes and activate NLRP3 (Jain et al, 2020). Thus, after thousands of years of development, MTB has coevolved with humans.…”
Section: Mechanisms Of Interaction Between Mtb Effector Proteins and ...mentioning
confidence: 99%